Post a New Question

algebra 1

posted by .

use substitution method
m+2n=1 5m+3n=-23
please step by step so that i could understand

  • algebra 1 -

    Substitution means we express one variable in terms of another, and substitute this expression into the second equation.

    m+2n=1 ...(1)
    5m+3n=-23 ...(2)

    From (1), we have
    subtract 2n from each side to get
    m=1-2n ...(1a)

    Substitute m from (1a) into (2) to get:
    5-10n+3n =-23
    -7n = -23 -5
    -7n = -28
    n=(-28)/(-7)=4 ...(2a)

    Substitute n from (2a) into (1a)
    So m=-7, n=4

    Last step!!
    Substitute the values of m and n into equations (1) and (2) to verify that the solutions are correct:

    m+2n=1 ...(1)
    -7+2*4=-7+8=1 OK

    5m+3n=-23 ...(2)
    =-23 OK

  • algebra 1 -

    THANKS!!!!!!! great explaining!!!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question